Climate change and income inequality in Sub-Saharan African countries - Mose, Naftaly; Boateng, Seth Acquah; Fumey, Michael Provide; Tanchev, Stoyan (Energy Economics Letters, 2025)
The potential for a feedback relationship between climate change and income inequality has become a concern in sub-Saharan African (SSA) countries due to its significant environmental and socio-economic impacts. This study aims to inform policymakers on ways to address inequality and climate resilience in the region simultaneously. It examines the relationship between climate change and income inequality in SSA countries, focusing on Kenya, Tanzania, and Uganda, by analyzing data from these three countries between 2009 and 2023. The Dumitrescu and Hurlin adaptation of the Granger causality test and pooled ordinary least squares research techniques were used in the analysis. The results of the pooled ordinary least squares model reveal that rising income inequality has a positive impact on climate change. Conversely, climate change exhibits a positive impact on income inequality. The Dumitrescu-Hurlin causality evidence indicates a strong, bidirectional relationship between climate change and income inequality in the three countries. This implies that the lagged value of climate change explains the variation in income inequality, with a feedback response where the lagged value of income inequality is instrumental in predicting climate change. The study suggests implementing inclusive economic growth and development policies aligned with climate mitigation measures and adaptation objectives.